Pesquisa de novo método de congelação para preservação do sêmen de ovinos Santa Inês - Lima, Fátima Revia Granja (2010)
Three experiments were carried out aiming to evaluate the influence of different factors on parameter of post-thawing semen motility and pregnancy index of rams. The first one showed the influence of extender type (skim milk, HEPES and TRIS), freezing temperature (-79oC, -90oC and -120oC) and final concentration of sperm (600 x 106, 800 x 106 and 1000 x 106 sperm per mL) on semen motility parameters of Santa Ines rams. The second one experiment evaluated the influence of egg yolk types (chicken and quail) and its percentage (10% and 20%) on the characteristics of motility of frozen semen of rams. The last one experiment evaluated the effect of two artificial insemination techniques (cervical and laparoscopic) on pregnancy rate of ewes of two farms. Pregnancy rate were compared within and between farms. Body condition score and parturity order influence on pregnancy rate was also analyzed. The results of experiment 1 showed that using milk extender, motility and speed of sperm were different (P<0.05 on -79°C temperature) when compared to other temperatures. Considering HEPES extender, the temperature of -90°C was lower compared to the others. Using TRIS extender, there was no difference between freezing temperatures, but the motility was higher when compared to the other extenders, at all temperatures evaluated. Considering sperm percentage, progressive motility and fast speed as variables, the concentration of 600 x 106sperm per mL proved to be higher (P<0.05) than 800 x 106 sperm per mL. Considering the mean velocity of rapid sperm trajectory(VAPR), the extender skim milk used at a temperature of -79°C presented a lower percentage when compared to other temperatures. However, TRIS extender was higher (P>0.05) when compare to the others. No difference was detected (P>0.05) between concentrations considering the other extenders. In experiment 2, the percentage of motile sperm was different (P<0.05) using TRIS extender (10% of chicken egg yolk). The variables progressive motility and rapid motility of spermatozoa presented the best rates, using TRIS (10% of chicken egg yolk) and did not differ (P>0.05) from TRIS (10% of quail egg yolk). It was observed a higher percentage (P<0.05) of sperm with head defects in the treatments with the highest percentage of egg yolk (20%), independently of the yolk type used. There was no statistical difference (P>0.05) in other morphological sperm changes. In experiment 3, artificial insemination type influenced on pregnancy rate, even with frozen semen, showing superior results (P<0.05) using laparoscopic via, on both farms. There was no effect (P>0.05) of parturity order on insemination techniques, on both farms. However, the body condition score (ECC) influenced the insemination using cervical via, on farm 1. Therefore, it was concluded that TRIS extender, at a freezing temperature of -79°C and final concentration of 600 x 106 sperm per mL, proved to be the freezing protocol more suitable for Santa Ines rams semen, using the TK 3000 equipment. The percentage of 10% of chicken egg yolk was the best to preserve sperm motility parameters, however the egg yolk of quail showed up as an alternative to be added to the semen extender. Despite the in vitro evaluation of frozen semen in this experiment have been satisfactory, it was not enough to increase the pregnancy rates of inseminated females. It was also concluded that laparoscopy technique is the most indicated when frozen semen is used, in ovine species.